Avaliação da atividade antitumoral e toxicológica do óleo essencial dos frutos de Xylopia langsdorffiana St. Hil. & Tul. (Annonaceae) - Moura, Ana Paula Gomes (2012)
The cancer is a complex genetic disorder, which results from concurrent changes in genes generally related to proliferation, differentiation and cell death. Natural products are widely used in the treatment of cancer. Xylopia langsdorffiana is a tree known popularly as "pimenteira-da-terra". The phytochemical study featured some essential oils with important biological activities, among them, the essential oil obtained from the fruits, which has as major constituents the α-pinene and limonene. This work aimed to evaluate the toxicity and antitumoral activity of the essential oil of fruits of X. langsdorffiana (O.E.X.), through in vitro and in vivo assays. The LC50 value obtained in the bioassay with A. salina was 459.0 μgmL. The CH50 value obtained in experiment of cytotoxicity in red blood cells (hemolysis) was 293.6 μgmL. Cytotoxicity test of O.E.X. with sulfarrodamina cell viability assessment in different tumor cell lines presented citotoxicity activity for the lineage of leukemia (K562), with TGI = 178 μg/mL. In addition the O.E.X presented significant cytotoxicity activity against cell lineage NCI/ADR-RES multiple-resistant ovarian with TGI = 45,38. The IC50 value obtained through the MTT assay in 180 Sarcoma cells was 145.1 μgmL. The LD50 value obtained in acute toxicity pre-clinical test was 351.09 mg/kg. In this study there was significant decrease in gain body mass in females treated with 250 mg/kg and in both sexes treated with 375 mg/kg, when compared with the control group. On the evaluation of in vivo antitumor activity, the tumor growth inhibition rates were, 38,7 and 54,3 % after treatment with 50 and 100 mg/kg of O.E.X. respectively. The toxicological analyses demonstrated no significant changes in the index of thymus after treatment with O.E.X., only an increase of spleen was verified. No changes was evidenced in the parameters of AST and ALT but it was demonstrated a slight hepatotoxicity in histopathological study for both treated groups with the O.E.X. The treatment with the O.E.X. not presented genotoxicity. In general, the changes are considered reversible and non-substantial when compared to those produced by several anticancer agents. Thus, it is possible to infer that O.E.X presented in vitro and in vivo antitumoral activity with moderate toxicity, which does not represent a limiting factor for its therapeutic applicability.